Systematic evaluation of plant metals/metalloids accumulation efficiency: a global synthesis of bioaccumulation and translocation factors - Huang, Wenbin; Zhang, Chengnian; Zhu, Bowei; Liu, Xiaoying; Xiao, Huxuan; Liu, Shibin; Shao, Huaiyong (Frontiers in Plant Science, 2025)
Phytoremediation, which involves the use of plants to accumulate and translocate metals and metalloids, represents a promising strategy for environmental remediation. The efficiency of phytoremediation is influenced by many factors such as metal/metalloid types, soil properties, and plant traits. It remains unclear how these factors modulate the efficiency of phytoremediation. We synthesized 547 data pairs from 82 studies to comprehensively evaluate the ability of hyperaccumulating plants to accumulate and translocate metals/metalloids under varying environmental conditions. The results show that cadmium (Cd), the most frequently investigated heavy metal, has the highest average bioaccumulation factor (BF) (10.0 ± 1.3) but a relatively low average translocation factor (TF) (1.8 ± 0.1). Aboveground biomass (AGB) of Cd hyperaccumulators is negatively correlated with BF but positively correlated with TF. Cd hyperaccumulating plants exhibit the highest accumulation capacity (maximal BF = 191), with roots outperforming aerial parts. The lower TF is mainly due to the lower AGB of Cd hyperaccumulating plants. In contrast, nickel (Ni) hyperaccumulators exhibit the highest TF, particularly in leaves and stems, indicating that Ni primarily accumulates in the aboveground parts. As soil pH increases, the BF of Cd and Zinc (Zn) decrease, whereas the BF of lead (Pb) increases, likely due to their distinct chemical behaviors under different pH conditions. Threshold concentrations were also identified for several for metals/metalloids (e.g., Cd: 214.8 mg kg-1; Pb: 31352.3 mg kg-1), beyond which BF falls below 1.0, indicating diminished accumulation efficiency due to toxicity constraints. In sum, these findings provide insights for optimizing phytoremediation strategies, aiding in plant selection and remediation condition optimization for improved efficiency and sustainability.